Nitrogen and phosphorus balance in soil with organic cultivation of legumes after incorporation of pigeonpea biomass - Alves, Sandra Maria Campos; Abboud, Antonio Carlos de Souza; Ribeiro, Raul de Lucena Duarte; Almeida, Dejair Lopes de (Pesquisa Agropecuaria Brasileira, 2004)
The objectives of this study were to evaluate the efficiency of pigeonpea (Cajanus cajan) biomass incorporation to the soil as well as the effect of presence or absence of pigeonpea hedgerows on soil fertility and productivity of three vegetables, beet, carrot and dwarf green bean. Samples were randomly taken in a block design with three replications for each crop. In the field, no other fertilization treatment was applied. In plots without biomass incorporation, nitrogen showed negative balance, whereas in the field with biomass incorporation a high positive N-balance was found. Concerning phosphorus, positive balances were determined in plots without biomass incorporation, however, the uptake of P increased significantly after biomass incorporation in all crops used. The results indicate that pigeonpea alley cropping system may represent an advantageous option for organic farmers to maintain or to improve soil fertility.